A COMPARISON OF THE DIVERSITY AND ABUNDANCE OF BRACONIDAE (HYMENOPTERA: ICHNEUMONOIDEA) IN THREE HIGHLANDS OF PENINSULAR MALAYSIA - H. A., Norliyana; Idris, A. B. (Malaysian Journal of Science, 2011)
A study on the abundance and diversity of Braconidae at Bukit Larut, Perak (BL), Cameron Highland, Pahang (CH) and Gunung Ledang, Johor (GL) was conducted from 13th October 2006 to 17th December 2006 using Malaise traps. A total of 57 individuals of Braconidae were successfully collected comprising of 12 subfamilies and 36 species. Braconids were most abundantly found in BL with 22 individuals, comprising of 15 individuals (8 subfamilies and 13 species) in upper part (600-900 m) and seven individuals (6 subfamilies and 7 species) in lower part (200-500 m) of the highland. Shannon-Weiner Index for divesrsity (H’) showed that there was no significant different (P>0.05) in species diversity between sites, with BL having the highest diversity value (H’=2.84), followed by GL (H’=2.75) and CH (H’=2.66). Species similarity between sites were low, ranging from 10% to 20% indicating great differences in biological and environmental factors between sites that influencing the fauna of Braconidae at these highlands. This study also shows that braconid wasps was more abundant in the undisturbed highland (BL) compared to the disturbed highland (CH and GL) (Key words: Braconidae, Hymenoptera, Diversity, Cameron Highland, Bukit Larut, Gunung Ledang